Identification of a potential interspecies reassortant rotavirus G and avastrovirus 2 co-infection from black-headed gull (Chroicocephalus ridibundus) in Hungary - Péter Pankovics; Károly Takáts; Péter Urbán; Róbert Mátics; Gábor Reuter; Ákos Boros (PLoS ONE, 2025)
The black-headed gull is the most common nesting gull species in Hungary. Based on the lifestyle and feeding habits of the black-headed gull, which is highly adapted to the human environment, they can be carriers and spreaders of potential human and other animal pathogens. Between 2014 and 2018 within the framework of the “Life Bird Ringing program” a total of 7 faecal samples were collected from gulls and one sample (MR04) was randomly selected for viral metagenomics and mass sequencing. 95.4% and 4% of the reads were classified into family Seadornaviridae and Astroviridae, respectively, and then were verified by RT-PCR method. In this study, the complete genome of a potential interspecies reassortant rotavirus (RV) strain gull/MR04_RV/HUN/2014 (PP239049-PP239059) and the partial ORF1ab, complete ORF2 of a novel avian nephritis virus strain gull/MR04_AAstV/HUN/2014 (PP239060) was discussed. The strain gull/MR04_RV/HUN/2014 was closely related to rotavirus G (RVG) viruses based on the proteins VP1–VP3, VP6, NSP2, NSP3, and NSP5, but it was more related to the human rotavirus B (RVB) strain Bang373 based on the NSP1, NSP4 and VP7, VP4 proteins, which is assumed to be the result of reassortment between different RVG-RVB rotavirus species. The strain gull/MR04_AAstV/HUN/2014 belonged to the genus Avastrovirus species avastrovirus 2 (AAstV-2) and is related to members of group 6 of avian nephritis viruses (ANVs), but based on the genetic distances it may be the first representative of a separate group. Additional gull samples were found to be negative by RT-PCR. Gulls, which are well adapted to the human environment, could potentially spread enterically transmitted viral pathogens like interspecies reassortant rotaviruses (RVG/RVB), but further molecular surveillance is needed to explore more deeply the viral communities of gulls or other related species adapted to human environments.